De Esclavos del Hospital a Sublevados Contra El Rey. La Integración de los Negros Esclavos de La Compañía de Jesús (Jujuy, Siglos XVII-XVIII) - Cruz, Enrique Normando (E- Revista de Estudos Interculturais, 2021)
This article studies the black salves of the Society of Jesus in the Tucuman district of Jujuy between the 17th and 18th centuries. From a cultural history perspective and using documentation not considered by other studies, the meaning of the hospital service and the term “bronzed” is necessary to define the black slave in the Ancient Régime. Secondly, the researcher describes the studied space and the period, and identifies black slavery in the different religious orders of the city. Finally, the article reviews the commercial insertion of the Jesuits in Jujuy, as well as the origin, use and final destination of the Society ́s black slaves, proposing the hypothesis that the local historical context and the Jesuit framework of domination enabled the full cultural integration of these actors of the colonial society.